Facies classification and patterns of lacustrine carbonate deposition of the Barra Velha Formation, Santos Basin, Brazilian Pre-salt - Gomes, J.P.; Bunevich, R.B.; Tedeschi, L.R.; Tucker, M.E.; Whitaker, F.F. (Marine and petroleum geology, 2020)
The lacustrine carbonate rocks of the giant Pre-salt oil-fields in the Santos and Campos Basins differ in a number of important aspects from classic lake deposits. Prior work has described distinctive and unusual features of deposition, early diagenesis and reservoir quality with in these rocks that defy classification using established schemes. In addition to their unusual textures, debate continues as to how to interpret the vertical stacking pattern of facies. A new facies classification scheme is proposed based on the relative abundance of three end-member components: mud (micrite and clay minerals), calcite spherulites and fascicular calcite shrubs. Although focused on the main textural and mineralogical features of the rocks as seen today, the proposed scheme takes into account the relative contribution of depositional and early diagenetic components, sediment mineralogy and the degree of dissolution. Application of this scheme offers insight into depositional conditions, whilst also linking to reservoir quality. Basic (elementary) cycles can be defined using this classification in combination with the variation in the abundance of detrital grains and the chemical composition. Three possible models are suggested to interpret the origin of the basic cycle within the Barra Velha Formation in the context of variation in climate, lake level and water chemistry. Integration of data from different sources, including petrographic, core description and chemical data for the basic cycle, offers improved process-based understanding of metre-scale facies patterns and provides a foundation for understanding larger scale vertical variations within and between unconformity-bound sequences. •A new facies classification scheme is proposed for lacustrine carbonates of the Pre-salt in the South Atlantic based on detailed analysis of the Aptian Barra Velha Formation. For in-situ facies, this is based on the proportion of three main components - calcite spherulites, calcite shrubs and mud, whereas for reworked facies Dunham's classification can be applied; mudstone facies are classified by mineral composition (calcite, dolomite, silica and Mg-clay).•The advantages of the proposed classification include the preservation of subtle changes in the abundance of components that may have been caused by depositional/diagenetic environmental changes. These have an impact on the process-based model and/or reservoir quality. The proposed classification can be used at a range of scales and offers the means to recognize systematic changes in the vertical distribution of facies classes that can be used as a basis for cyclicity analysis.•The Barra Velha Formation consists of two major facies types: a mud-rich facies (the non-reservoir interval) occurring mainly in deeper-water areas around the Santos palaeo-high, and a mud-poor facies, more common in the shallow-water areas (the reservoir interval).•Bulk chemical analyses combined with detrital grain content provide valuable additional environmental information. Three possible interpretations are suggested, incorporating not just the main components present but also considering the mechanisms by which detrital grains were transported into the basin and the lake chemistry. (1) Humid to arid climate, fluctuating lake-level model. (2) Semi-arid to arid climate, shallow-lake model. (3) Constant lake level controlled by a spill-point. Whereas in marine carbonate systems, facies variations may be interpreted largely in terms of accommodation, within alkaline lake systems the role of temporal fluctuations in lake-water chemistry may be equally important.